Pengaruh Kreatıvıtas Mengajar Guru Dan Mınat Belajar Terhadap Hasıl Belajar Sıswa Sekolah Dasar - Johanes D.C Karundeng; Widdy H.F Rorimpandey; Martinus M Krowin (Jurnal Elementaria Edukasia, 2023)
ABSTRACT The low learning outcomes of elementary school students are the basis for evaluation creativity teachers in the learning process in the classroom. Apart from that, interest in learning is also an aspect that needs to be improved for students to achieve good learning outcomes. This research is quantitative research with a correlational type. The population of this study was the fifth-grade students at Posilangon State Elementary School, totaling 32 students. The research sample consisted of 32 students who were determined using techniques non probability sampling. The data collection techniques used were questionnaires and documentation. Test the validity of the instrument items using product moment, test the reliability of the instrument using alpha cronbach. The data analysis technique in this research uses descriptive statistical analysis, research prerequisite tests, and hypothesis testing. Prerequisite tests include normality tests, linearity tests, homogeneity and multicollinearity tests. Hypothesis testing uses simple linear regression tests and multiple linear regression tests. research results show that: 1) creativity Teacher teaching has a positive and significant influence on science learning outcomes with a variable contribution of 24.2%. 2) students' interest in learning has a positive and significant influence on science learning outcomes with a variable contribution of 99.5%. 3) creativity Teacher teaching and student interest in learning simultaneously have a positive and significant influence on science learning outcomes with a variable contribution of 44.5%.